2020
DOI: 10.3390/en13123129
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Flow in a Kaplan Turbine Model during Transient Operation from the Best Efficiency Point to Part Load

Abstract: The aim of this study is to develop a reliable numerical model that provides additional information to experimental measurements and contributes to a better exploitation of hydraulic turbines during transient operation. The paper presents a numerical analysis of the flow inside a Kaplan turbine model operated at a fixed runner blade angle during load variation from the best efficiency point (BEP) to part load (PL) operation. A mesh displacement is defined in order to model the closure of the guide vanes. Two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
(66 reference statements)
1
15
0
Order By: Relevance
“…A comparative time-step sensitivity study on the Francis-99 model complete turbine domain and turbine with passage domain were performed by Sotoudeh et al [19]. A similar time-step sensitivity study was performed by Iovanel et al [20] on the Kaplan turbine numerical model with one guide vane passage domain and a complete runner-draft tube domain. The results of both studies confirmed that with larger time-step and reduce geometry modeling, the RVR frequency was captured accurately.…”
Section: Authorsmentioning
confidence: 99%
See 4 more Smart Citations
“…A comparative time-step sensitivity study on the Francis-99 model complete turbine domain and turbine with passage domain were performed by Sotoudeh et al [19]. A similar time-step sensitivity study was performed by Iovanel et al [20] on the Kaplan turbine numerical model with one guide vane passage domain and a complete runner-draft tube domain. The results of both studies confirmed that with larger time-step and reduce geometry modeling, the RVR frequency was captured accurately.…”
Section: Authorsmentioning
confidence: 99%
“…However, the amplitude of the RVR frequency largely depends on the time-step considered. More specifically, for smaller time-steps, larger RVR amplitude was observed and vice versa [20]. A literature review on numerical techniques applied to hydro-turbines done by Trivedi et al [3] concluded that it still is quite challenging to obtain an accurate prediction of pressure amplitudes in the hydro-turbines, especially with RANS turbulence models.…”
Section: Authorsmentioning
confidence: 99%
See 3 more Smart Citations